2012
DOI: 10.1007/s10577-012-9294-z
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four chromosome FISH in human IVF embryos reveals patterns of post-zygotic chromosome segregation and nuclear organisation

Abstract: Fluorescence in situ hybridisation (FISH) was first applied on in vitro fertilisation (IVF) embryos for the preimplantation genetic diagnosis of sex, then chromosome translocations and later for chromosome copy number (PGS). Because of the controversy surrounding PGS diagnostically, it has been replaced by array-based approaches; however, FISH remains a powerful tool for investigating mechanisms of both post-zygotic segregation error and nuclear organisation, especially if most or all of the chromosomes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 90 publications
0
14
0
1
Order By: Relevance
“…Given the fact that aneuploidy could affect any chromosome (Franasiak et al 2014), FISH cannot reliably detect a significant proportion of the aneuploidies and segmental abnormalities present in embryos. Although there have been attempts to analyze 24 chromosomes by using FISH technique on human embryos (Ioannou et al 2011, Ioannou et al 2012, such an approach was fraught with technical problems, for example overlapping signals, failed probes and so forth, relegating it to the realms of a research tool only for investigating, for example nuclear organization and mosaicism when multiple cells are available for analysis (Turner et al 2016). Other limitations include the success of the technique being dependent on the experience of the laboratory personnel performing critical laboratory procedures including embryo biopsy, blastomere fixation and analysis.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that aneuploidy could affect any chromosome (Franasiak et al 2014), FISH cannot reliably detect a significant proportion of the aneuploidies and segmental abnormalities present in embryos. Although there have been attempts to analyze 24 chromosomes by using FISH technique on human embryos (Ioannou et al 2011, Ioannou et al 2012, such an approach was fraught with technical problems, for example overlapping signals, failed probes and so forth, relegating it to the realms of a research tool only for investigating, for example nuclear organization and mosaicism when multiple cells are available for analysis (Turner et al 2016). Other limitations include the success of the technique being dependent on the experience of the laboratory personnel performing critical laboratory procedures including embryo biopsy, blastomere fixation and analysis.…”
Section: Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…4). In mosaic embryos, the greater prevalence of monosomy over trisomy has implicated anaphase lagging as the main mechanism of formation of mosaicism in embryos (Coonan et al 2004, Ioannou et al 2012, Capalbo et al 2013a. More recently, generation of micronucleus (small nucleus like structures) subsequent to the appearance of lagging chromosomes has been proposed as a novel mechanism for the formation of mosaicism in mouse embryos (Vázquez-Diez et al 2016).…”
Section: Mosaicismmentioning
confidence: 99%
“…In the absence of a reciprocal pattern for each (i.e., a corresponding trisomy and monosomy of the same chromosome) we would infer that the +14, +15, and +21 aneuploidies arose via independent chromosome gain (perhaps some mechanism involving endoreduplication) and the monosomies -7, -10, -11, -13, and -19 by an independent chromosome loss (anaphase lag). Utilizing FISH, Delhanty et al [1997] and Ioannou et al [2012] demonstrated a lack of mitotic non-disjunction (3 + 1 pattern), suggesting that it is a rare mechanism for post-zygotic aneuploidy in human development. More recent data utilizing CCS support the notion that non-disjunction is a uncommon event, demonstrating that chromosome losses occur at a 4-fold higher rate than chromosome gains [McCoy et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic alterations in children conceived after assisted reproduction can be attributed to epigenetic errors from manipulation of the embryo culture that follows IVF [Cetin et al, 2003], to the effects of controlled ovarian hyperstimulation and ovulation induction, in vitro sperm preparation, or an inherent defect in the infertile couple possibly leading to both the infertility and the birth defect [Olson et al, 2005]. Thus, it is difficult to draw general conclusions about the overall levels of chromosome abnormality in embryos generated by IVF [Ioannou et al, 2012]. In our patient, the deletion could be either the result of manipulation or a sporadic event not directly related to IVF.…”
Section: Discussionmentioning
confidence: 99%